PEMBELAJARAN BAHASA ARAB PADA PERGURUAN TINGGI AGAMA ISLAM DI INDONESIA - Bulkisah Bulkisah (Jurnal Ilmiah Didaktika, 2012)
As a means of communication among the nations of the world, especially the unity of Muslims worldwide, Arabic occupies a strategic position because it can support the understanding of the religion of Islam itself. Therefore, learning the Arabic language at the college level religion of Islam became a necessity because in addition to a scientific transformation of the classical repertoire Intellectual period, pertegahan and modern, Arabic language is also used as the language of scientific, academic as well as popular language.